Stereotactic total ablative radiotherapy with MR-LINAC for synchronous oligometastatic prostate cancer - Poon, Darren MC.; Yuan, Jing; Wong, Oi Lei; Yang, Bin; Chiu, Sin Ting; Cheung, Kin Yin; Chiu, George; Yu, Siu Ki (Frontiers in Oncology, 2025)
ObjectivesTo prospectively investigate the feasibility, toxicity, and preliminary clinical outcomes of magnetic resonance (MR)-guided stereotactic total ablative radiotherapy (MRgSTAR) for simultaneous treatment of the prostate and pelvic bone metastases in patients with synchronous oligometastatic prostate cancer (OMPC).MethodsThis study included patients with histologically confirmed synchronous OMPC, defined as ≤ 5 lymph node or pelvic bone metastases identified via prostate-specific membrane antigen positron emission tomography (PSMA-PET). Real-time adaptive MRgSTAR was delivered using a 1.5T MR-integrated linear accelerator (MR-LINAC) in five fractions, administered twice weekly, targeting the prostate (33.5–40 Gy) and nodal/bone metastases (36.5–40 Gy) simultaneously. Androgen-deprivation therapy (ADT) was initiated prior to MRgSTAR, with the addition of androgen receptor pathway inhibitor (ARPI) at the physician’s discretion. Adverse events (AEs) were assessed using the Common Terminology Criteria for AEs v5.0, and tumor response was evaluated per the Response Evaluation Criteria in Solid Tumors v1.1. Progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan–Meier method, with log-rank tests used to explore clinical factors associated with survival outcomes.ResultsForty-three patients underwent MRgSTAR, with a median follow-up of 36.5 months (range: 15.4–57.6 months). ADT combined with ARPI therapy was administered in 22 patients (52%). All patients completed the five-fraction regimen. Biochemical progression occurred in three patients, of whom two had out-of-field metastases and one had local progression as per follow-up PSMA-PET. The estimated 3-year OS and PFS rates were 100% and 95.2% (95% confidence interval: 89.0%–100%), respectively. No clinical factors, including ARPI use, significantly correlated with survival outcomes. No radiotherapy-related AEs of grade ≥ 3 were observed.ConclusionMRgSTAR demonstrates promising early survival outcomes and a favorable toxicity profile in synchronous OMPC, warranting further investigation to confirm its therapeutic role.